Dasar kerajaan dalam membangunkan industri pertahanan Malaysia: analisis masalah, cabaran dan prospek - Mohamed Fajil, Abdul Batau (2021)
The National Defense Industry Policy which was first introduced in 1970 is one of the components of Malaysia’s National Defense Policy (DPN). The implementation of the DIPN has raised questions and criticisms among various quarters. This is because there are issues that say the policy is weak and fails to produce domestic defense assets in meeting the needs of the Malaysia Armed Forces (ATM). Capability and capacity of the Malaysian defense industry in producing the country’s defense assets are still a matter of dispute and problem at the national level. Local defense industry has failed to produce adequate defense assets despite several policies have been formulated to develop this industry. This study analyzes the development needs of the Malaysian defense industry in an effort to attain the objective of independent defence (Defense self-reliance) as enshrined in the DPN. The purpose of this study is to identify and discuss the factors, problems, challenges and development of the Malaysian defense industry. This study uses a qualitative method involving triangulation method for the collection of primary and secondary data, as well as using interview method with the Minister of Defense of Malaysia, Deputy Minister of Defense of Malaysia, senior officers of the ATM and the public. The findings of the study show that the implementation of developing Malaysia’s defense industry is weak and has failed to achieve its goals. This is because the components in the development of the local defense industry show weaknesses and this also has an impact on the overall development of the Malaysian defense industry. Therefore, this study provides some suggestions in strengthening the components of defense industry to ensure that the objectives of developing the Malaysian defense industry can be achieved effectively. Among these suggestions include improving the DIPN framework, increasing the research and development budget, monitoring the progress and expertise of research and development, increasing marketing and commercialization of defense assets, as well as expanding cooperation network with foreign countries should be given priority by the government accordance with objectives of DPN in defending national security through the development of developing National Defense Industry.